Conserving what and for whom? why conservation should help meet basic human needs in the tropics - Kaimowitz, D.; Sheil, Douglas (2007)
For hundreds of millions of people, biodiversity is about eating, staying healthy, and finding shelter. Meeting these people’s basic needs should receive greater priority in the conservation agenda.Wild and semi-wild plants and animals contribute significantly to nutrition, health care, income, and culture in developing countries, and the poorest and most vulnerable people often rely on those resources most. Depleting those resources or making them inaccessible can impoverish these people even further. ‘Pro-poor conservation’—that is, conservation that aims to support poor people—explicitly seeks to address basic human needs. Such an emphasis has many potential synergies with more conventional conservation goals. Nonetheless, pro-poor conservation requires a distinct attitude to gauging conservation outcomes and a different approach to conservation science. Biologists can make a vital contribution.